2000
DOI: 10.1038/sj.bmt.1702699
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in severe acquired aplastic anemia of childhood

Abstract: Summary:Multi-agent immunosuppressive therapy has produced improved survival for severe acquired aplastic anemia in children. Recently, some investigators have suggested that immunosuppressive therapy may replace bone marrow transplantation as first-line therapy for this disorder. To assess its validity, we compared the outcomes of bone marrow transplantation vs immunosuppressive therapy in one institution from 1987 to 1997. We studied 46 consecutive patients less than 18 years of age who presented between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…2,3 Long-term survival of approximately 85%-100% has been observed for younger patients after BM transplantation from HLA-identical siblings after a preparative regimen with cyclophosphamide and antithymocyte globulin (CY Ď© ATG) followed by posttransplantation immunosuppression with methotrexate and cyclosporine (MTX Ď© CSP). 2,[4][5][6] As can be seen in Burroughs et al's report, 7 5-year survival after 1981 is 95%-100% for children who underwent transplantation at Fred Hutchinson Cancer Research Center (FHCRC).…”
Section: Introductionmentioning
confidence: 84%
“…2,3 Long-term survival of approximately 85%-100% has been observed for younger patients after BM transplantation from HLA-identical siblings after a preparative regimen with cyclophosphamide and antithymocyte globulin (CY Ď© ATG) followed by posttransplantation immunosuppression with methotrexate and cyclosporine (MTX Ď© CSP). 2,[4][5][6] As can be seen in Burroughs et al's report, 7 5-year survival after 1981 is 95%-100% for children who underwent transplantation at Fred Hutchinson Cancer Research Center (FHCRC).…”
Section: Introductionmentioning
confidence: 84%
“…Of 3,085 retrieved publications, 358 full-text papers were obtained for further assessment and 26 non-randomized controlled clinical trials were identified that met the inclusion criteria and were included in the present study [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56]. We did not identify any RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Patients were recruited between 1970 and 2002 in 24 studies, whereas in 2 studies, year of treatment was not reported. In 13 studies [31], [34], [35], [39], [41], [42], [43], [44], [45], [46], [47], [49], [54], disease severity (SAA or VSAA) or first-line treatment was clearly classified for all patients. The proportion of patients with moderate aplastic anemia, unknown disease severity, or second-line treatment was less than 20% in 6 studies [32], [36], [38], [40], [50], [52] and was 20% or more in 7 studies [33], [37], [48], [51], [53], [55], [56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressive therapy using the combination of antithymocyte globulin (ATG), cyclosporin and methyprednisolone is indicated for other children who have no HLA compatible sibling [25,26]. Overall survival at 5 years is estimated at about 80%, but the eventfree survival rate is lower as a result of non response or relapse.…”
Section: Discussionmentioning
confidence: 99%